Plan estratégico de enseñanza para atender las NEE en los estudiantes de la Unidad Educativa Jaime Roldos Aguilera, Montalvo - Lucio Erazo, Gladys (2022)
The research focuses on serving students who have diverse characteristics and are associated with disabilities such as intellectual, physical-motor, auditory, visual or mental; multi-disabilities; and generalized developmental disorders and those that are not associated with disability such as dyslexia, dyscalculia, dysgraphia, dysorthography, dysphasia, attention deficit and hyperactivity disorders, behavior disorders, the idea is that with the contribution of the strategic teaching plan, improve their learning and that the didactic strategies applied will improve their lifestyle, their quality and warmth, including all not only for certain students and can contribute to the exchange of lived experiences that serve to help solve the problems they face in daily life. In the strategic teaching plan, one of the important factors is the work of the teacher and their motivation, which directly influences students with special educational needs, they must exchange and guide their experiences in this way, it is possible to work as a team and students with needs special educational programs will have better attention and thus the teacher will develop a better teacher evaluation, it will always be a stimulus, becoming part of the motivational strategies for student learning.